Exploring the FDA Adverse Event Reporting System to Generate Hypotheses for Monitoring of Disease Characteristics. Issue 5 (21st January 2014) - Fang, H; Su, Z; Wang, Y; Miller, A; Liu, Z; Howard, P C; Tong, W; Lin, S M
<x xml:space="preserve">Abstract</x> The US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) is a database for postmarketing drug safety monitoring and influences changes in FDA safety guidance documents such as drug labels. The number of cases in the FAERS has rapidly increased with the improvement of submission methods and data standards and thus has become an important resource for regulatory science. Although the FAERS has been predominantly used for safety signal detection, this study explored its utility for disease characteristics. Clinical Pharmacology & Therapeutics (2014); 95 5, 496–498. doi:10.1038/clpt.2014.17